Розвиток словацької етнографії в міжвоєнний період (1918-1939) - Леньо, П. (Народна творчість та етнографія, 2005)
The period of time from 1918 to 1939 is an important time for Slovak ethnography which deserves special attention from researches. During this time we can follow the liberation from Austro-Hungarian regime and receiving of official status and form a part of First Czech-Slovak Republic which influenced the development of science in the country. The author is looking at the topic of development of ethnography in two different ways. First, it is the work of ethnographical societies and individual ethnographers. Second, it is the development of the methodological base during this period of time. The author came to following conclusions: during 1920-30th there were some tendencies to create more professional ethnographical science. One of the main deficiencies of this time was the absence of specific purpose of the ethnographer's work which they would prescribe for themselves in order to distinguish ethnography among other disciplines. A positive moment was the creation of folk museums, intensive contacts with scholars from Chech republic. But until the second half of the 20th Century ethnography was sub discipline, with the description as the main method of work.